Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1071/wf07086
|View full text |Cite
|
Sign up to set email alerts
|

The BlueSky smoke modeling framework

Abstract: Smoke from fire is a local, regional and often international issue that is growing in complexity as competition for airshed resources increases. BlueSky is a smoke modeling framework designed to help address this problem by enabling simulations of the cumulative smoke impacts from fires (prescribed, wildland, and agricultural) across a region. Versions of BlueSky have been implemented in prediction systems across the contiguous US, and land managers, air-quality regulators, incident command teams, and the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
163
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(175 citation statements)
references
References 15 publications
0
163
0
Order By: Relevance
“…CW-FIS uses fire hotspots detected by NASA's Moderate Resolution Imaging Spectroradiometer (MODIS) and NOAA's Advanced Very High Resolution Radiometer and Visible Infrared Imaging Radiometer Suite imagery as inputs. Daily total emissions per hotspot are then estimated by the Fire Emission Production Simulator module of the BlueSky modelling framework (Larkin et al, 2009). SMOKE was then used to prepare model-ready hourly emissions of several species (including NH 3 ) in a point-source format for model input.…”
Section: Addition Of Forest Fire Emissionsmentioning
confidence: 99%
“…CW-FIS uses fire hotspots detected by NASA's Moderate Resolution Imaging Spectroradiometer (MODIS) and NOAA's Advanced Very High Resolution Radiometer and Visible Infrared Imaging Radiometer Suite imagery as inputs. Daily total emissions per hotspot are then estimated by the Fire Emission Production Simulator module of the BlueSky modelling framework (Larkin et al, 2009). SMOKE was then used to prepare model-ready hourly emissions of several species (including NH 3 ) in a point-source format for model input.…”
Section: Addition Of Forest Fire Emissionsmentioning
confidence: 99%
“…However, inclusion of fire emissions in the model did not allow improving temporal variability of AOT data at specific locations of the AERONET monitoring network. Larkin et al (2009) presented a modeling framework enabling simulations of the cumulative smoke impacts from fires across the USA. They showed that the modeled output generally compared well with satellite plume observations, but underpredicted measured PM 2.5 concentrations during the considered episode.…”
mentioning
confidence: 99%
“…They showed that the modeled output generally compared well with satellite plume observations, but underpredicted measured PM 2.5 concentrations during the considered episode. While Wang et al (2006), Hodzic et al (2007) and Larkin et al (2009) used wildfire emission inventories based on the burned area approach, Sofiev et al (2009) derived aerosol fire emissions from FRP measurements. Their emission estimates were then used in the SILAM CTM to simulate PM 2.5 concentrations and columns.…”
mentioning
confidence: 99%
“…Pursuant to the need for an alternative to CMAQ, scientists developed the BlueSky framework to meet the need of accurately forecasting smoke dispersion and settling (Larkin et al,2009). BlueSky ( Figure 3-42) is a framework that contains and combines models and data about weather, fires and fuels, emissions, and terrain.…”
Section: Bluesky Frameworkmentioning
confidence: 99%